2011
DOI: 10.1016/j.cytogfr.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of TGF-β and epithelial-to mesenchymal transition in diabetic nephropathy

Abstract: Transforming Growth Factor-beta (TGF-β) is a pro-sclerotic cytokine widely associated with the development of fibrosis in diabetic nephropathy. Central to the underlying pathology of tubulointerstitial fibrosis is epithelial-to-mesenchymal transition (EMT), or the trans-differentiation of tubular epithelial cells into myofibroblasts. This process is accompanied by a number of key morphological and phenotypic changes culminating in detachment of cells from the tubular basement membrane and migration into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
187
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 128 publications
4
187
0
1
Order By: Relevance
“…On the other hand, Yang et al (18) demonstrated that the threshold for the TGF-β1 response was reduced significantly by the complete depletion of SnoN and that a minimal amount of TGF-β1 was sufficient to trigger a full-scale TGF-β1 response under chronic disease conditions. It is widely accepted that hyperactive TGF-β1 signaling plays a crucial role in the genesis and progression of diabetic renal injuries (11,12,19). Thus, it is possible that the downregulation of SnoN protein expressino under high-glucose conditions may lead to hyperactive TGF-β1/Smad signaling and promote the pathogenesis of DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Yang et al (18) demonstrated that the threshold for the TGF-β1 response was reduced significantly by the complete depletion of SnoN and that a minimal amount of TGF-β1 was sufficient to trigger a full-scale TGF-β1 response under chronic disease conditions. It is widely accepted that hyperactive TGF-β1 signaling plays a crucial role in the genesis and progression of diabetic renal injuries (11,12,19). Thus, it is possible that the downregulation of SnoN protein expressino under high-glucose conditions may lead to hyperactive TGF-β1/Smad signaling and promote the pathogenesis of DN.…”
Section: Discussionmentioning
confidence: 99%
“…High glucose activates TGF-β1 signaling, which in turn stimulates tubule epithelial cells to overproduce extracellular matrix (10). A large body of evidence has indicated that TGF-β1 plays a critical role in the development of tubulointerstitial fibrosis in DN (4,[10][11][12]. However, the molecular mechanisms underlying the role of TGF-β1 in the pathogenesis of DN remain elusive.…”
mentioning
confidence: 99%
“…As summarised in a recent review, TGF-β1 binds to a trans-membrane TGF-β receptor II (TBRII) and initiates several intracellular signalling cascades, including small mothers against decapentaplegic (SMAD) and mitogen-activated protein kinases such as extracellular regulated kinase, p38 and Jun kinase [42]. SMADs are subdivided into three classes: (1) receptor regulated SMADs (SMAD1, -2, -3, -5 and −8); (2) the common SMADs (SMAD4); and (3) the inhibitory SMADs (SMAD6 and −7) [43].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β signaling is critical in promoting liver fibrosis (15,16). While, according to the results of the present study, inhibition by S17902 and POP overexpression did not affect TGF-β1 expression and p-Smad2/3 levels in HSC-T6 cells, POP participated in the regulation of Smad7 levels.…”
Section: Discussionmentioning
confidence: 57%
“…Among these Prolyl oligopeptidase attenuates hepatic stellate cell activation through induction of Smad7 and PPAR-γ growth factors, TGF-β1 is recognized as a major profibrogenic cytokine by promoting and maintaining HSC activation, proliferation, as well as collagen production and deposition through the TGF-β/Smad pathway (15)(16)(17)(18). Peroxisome proliferator activated receptor-γ (PPAR-γ) was initially identified as a key regulator of adipogenesis (19), while increasing evidence has confirmed that PPAR-γ is a key factor in HSC activation and phenotypic alteration, maintaining HSCs in a quiescent phase, and suppressing the production of type I collagen, α-SMA and TGF-β1.…”
Section: Introductionmentioning
confidence: 99%